Constant Light Exposure Alters Gut Microbiota and Promotes the Progression of Steatohepatitis in High Fat Diet Rats - Wei, Lin; Yue, Fangzhi; Xing, Lin; Wu, Shanyu; Shi, Ying; Li, Jinchen; Xiang, Xingwei; Lam, Sin Man; Shui, Guanghou; Russell, Ryan; Zhang, Dongmei (Frontiers in Microbiology, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) poses a significant health concern worldwide. With the progression of urbanization, light pollution may be a previously unrecognized risk factor for NAFLD/NASH development. However, the role of light pollution on NAFLD is insufficiently understood, and the underlying mechanism remains unclear. Interestingly, recent studies indicate the gut microbiota affects NAFLD/NASH development. Therefore, the present study explored effects of constant light exposure on NAFLD and its related microbiotic mechanisms. Material and method: Twenty-eight SD male rats were divided into four groups (n=7 each): rats fed a normal chow diet, and exposed to standard light-dark cycle (ND-LD); rats fed a normal chow diet, and exposed to constant light (ND-LL); rats fed a high fat diet, and exposed to standard light-dark cycle (HFD-LD); and rats on a high fat diet, and exposed to constant light (HFD-LL). Body weight, hepatic pathophysiology, gut microbiota, and short/medium chain fatty acids in colon contents, serum lipopolysaccharide (LPS) and liver LPS-binding protein (LBP) mRNA expression were documented post intervention and compared among groups. Result: In normal chow fed groups, rats exposed to constant light displayed glucose abnormalities and dyslipidemia. In HFD-fed rats, constant light exposure exacerbated glucose abnormalities, insulin resistance, inflammation and liver steatohepatitis. Constant light exposure altered composition of gut microbiota in both normal chow and HFD fed rats. Compared with HFD-LD group, HFD-LL rats displayed less Butyricicoccus, Clostridium and Turicibacter, butyrate levels in colon contents, decreased colon expression of occludin-1 and zonula occluden‐1 (ZO-1) , and increased serum LPS and liver LBP mRNA expression. Conclusion: Constant light exposure impacts gut microbiota and its metabolic products, impairs gut barrier function and gut-liver axis, promotes NAFLD/NASH progression in HFD rats.